Building a proposed educational program based on the principles of free writing and measuring its impact on improving reflective thinking skills and writing fluency for basic stage female students in Jordan. (Journal of the College of Basic Education, 2022)
This study aims at building an educational program based on Free Writing, and examining its effect on Binary-Thinking Skills and Writing Fluency for elementary female students in Jordan.Two schools have been chosen, and in each one 25 students were selected, so this study was applied on 50 students in sum from two public schools in amman`s qasaba, during the second semester of the academic year 2014/2015.The selected students were separated into two groups: one experimental group and the other is control group. The searcher prepared two tests: one in Binary-Thinking Skills and one in Writing-Fluency Skills each has 30 open-ended questions. The two test were confirmed for reliability. The reliability of the Binary-Thinking test was (0.88) and (0.86) for Writing-Fluency test. Analysis of the results was based an mean and standard deviations calculations of answer to each question and the ANOVA statistical analysis was used. The results showed statistically significant differences at (α=0.05) in the level of Binary-Thinking and Writing-Fluency skills of the experimental group that was studied according to the educational program.